БАСШЫЛАРДА ӘДАЛАТ ПАЗЫЙЛЕТИН ҚӘЛИПЛЕСТИРИЎ ҲƏМ ОНЫҢ ЖОЛЛАРЫ - Ережепов, М.Т. (SCIENCE and SOCIETY, 2021)
The article examines the development and management practices in all areas, with leaders running the state and other sectors based on the principles of justice. Opinions on the rule of law, the development of the country, and the well-being of people are presented. Also, the article discusses many examples from the book "Temur’s Charter".